Health applications for corporate health management - Steigner, Guido; Thielscher, Christian (Telemedicine and e-health, 2017)
Introduction: Many corporate organizations around the world are looking at new ways to improve the health and well-being of their employees. Many have begun to use m-health approaches and unique applications (apps) to provide assistance. In Germany, both m-health and occupational health management (OHM) are growing quickly. Therefore, we hypothesized that the combination -apps usage in OHM - is growing as well. We studied the usage of health apps in large corporations for health management of employed individuals. Methods: To understand the environment in Germany, a two-part study was conducted. First, an extensive literature search was done and second, interviews were conducted with 12 of the 20 biggest companies' health management representatives.Results:Using key search terms, 5,445 peer-reviewed journal articles traced with German databases and on PubMed were reviewed. Interestingly and somewhat surprising to the authors, none of them covered our specific topic. Interviews were conducted with 60% of the companies indicated. Only 3 out of 12 companies use apps. Four companies are piloting apps. With one exception, apps cover well-known areas such as food coaching, physical motion, smoking cessation, stress prevention, and other health-related subjects. One app used sensors in work clothing to prevent unhealthy motion. With a few exceptions, there has been no evaluation of the utility and utilization of apps. Discussion: Current app usage in corporate health management in Germany is surprisingly low. Apps need to be better evaluated.